PENGARUH VIDEO TERHADAP PENGETAHUAN SISWA DI KOTA (STUDI PADA SISWA SMP NEGERI 1 CIRUAS, BANTEN) - Vina Mahdalena; Lusia Handayani (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
Learning by using other media that is more interesting such as video (audio visual) can be tested on junior high school students because it has strengths and abilities that we can use to overcome existing limitations. This study aims to compare the knowledge of students in villages and cities when they are given material using video media. The method used is the pre and post test experiments. The results showed that the video learning media had a positive impact on learning outcomes because it was proven to increase student knowledge. However, in the case of students in rural schools the increase in knowledge was not as significant as in the cities. Video learning media have higher posttest scores on students in cities than students in villages. Furthermore, a very significant difference is shown in testing students' knowledge in cities and villages when given material exposure using video media. So, students in cities are more prepared to be given other learning methods such as video shows compared to students in villages. The development of learning methods with digital video media is more effective in students in cities than in villages.